1997
DOI: 10.1046/j.1365-2850.1997.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Case management: a week in the life of a clinical case management team

Abstract: This paper describes the work of a clinical case management core team (four nurses and an occupational therapist) during the course of a week. Information was gathered through non-participant observation of the team by two independent researchers. Transcripts produced from the data recorded were examined. From this, seven categories of activity were identified: planned client contact; unplanned client contact; family/carer contact; liaison; administration; team information sharing and supervision, training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, when it comes to research in this area, occupational therapists seem to have concentrated on providing clinical supervision mainly to occupational therapy assistants and occupational therapy students, and there is practically no research focusing on the occurrence of or need for receiving clinical supervision. However, Waite et al (31) reported, from an investigation of typical work activities of a case management core team of four nurses and one occupational therapist, that team information sharing and supervision was one out of seven typical activities during a week. The study by Gahnstrom-Strandqvist et al (11) indicated that support and supervision from leaders were positively associated with job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, when it comes to research in this area, occupational therapists seem to have concentrated on providing clinical supervision mainly to occupational therapy assistants and occupational therapy students, and there is practically no research focusing on the occurrence of or need for receiving clinical supervision. However, Waite et al (31) reported, from an investigation of typical work activities of a case management core team of four nurses and one occupational therapist, that team information sharing and supervision was one out of seven typical activities during a week. The study by Gahnstrom-Strandqvist et al (11) indicated that support and supervision from leaders were positively associated with job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…As Hudson (2002) notes, working in close proximity to each other in a shared office aids this communication process. Apart from the benefits to clients, team communication and training could also enable care managers to reflect on and cope with stressful situations (Waite et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Ross & Tissier (1997) list needs assessment, care planning, implementing care plans, monitoring services and reviewing as some of the core tasks. Waite et al (1997) uncovered several categories of main activity, as follows: planned direct client contact (25%); unplanned direct client contact (10%); liaison with other services (5%); administration (17%); family/carer work (1%); information sharing with team members (13%); and supervision and training (16%). Gorman (2000) identified essential care manager skills, such as communication, collaboration, partnership working, negotiation, conflict resolution, and reflective working.…”
Section: Introductionmentioning
confidence: 99%
“…The study sought to record the natural activity of the ward round in an unobtrusive way with the emphasis on verbatim accounts. A similar method of investigation has previously been used successfully to investigate the functioning of a psychiatric team (Waite et al, 1997). Consideration was given to tape recording of discussion but this was not done for two reasons.…”
Section: Methodological Issuesmentioning
confidence: 99%